2021
DOI: 10.1111/1556-4029.14685
|View full text |Cite
|
Sign up to set email alerts
|

Modeling allelic analyte signals for aSTRs in NGS DNA profiles

Abstract: Points of view in this document are those of the authors and do not necessarily represent the official position or policies of their organizations.Names of commercial manufacturers are provided for identification purposes only, and inclusion does not imply endorsement of the manufacturer, or its products or services by the FBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…where authors modeled allelic signals of sequenced data. Results indicated that locus‐specific variances could improve modeling of sequencing data based on different locus amplification efficiencies [39]. Additional data, as well as more variety in the sample profile of true biological samples would be of benefit to further evaluate the relationship between variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…where authors modeled allelic signals of sequenced data. Results indicated that locus‐specific variances could improve modeling of sequencing data based on different locus amplification efficiencies [39]. Additional data, as well as more variety in the sample profile of true biological samples would be of benefit to further evaluate the relationship between variables.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these results suggest that evaluation should be performed considering the number, quality, and type of samples pooled together for sequencing when modeling allelic drop‐out and how these variables affect the optimal read count range, which is approximately 85,000 reads/sample with the ForenSeq™ DNA Signature Prep Kit [41, 42]. Degradation was found to also be important when modeling allelic drop‐out [39, 47]. Additionally, a quantitation cut‐off value may be useful to determine when to sequence a low‐level sample separately or with other lower‐level samples to optimize the amount of genetic data generated instead of batching with optimal level samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3) Marker efficiency: As provided by [61], we included locus-specific marker efficiency parameters. This was achieved by scaling the shape argument of the gamma distribution with a marker specific parameter.…”
Section: Extension Of the Euroformix Model (Mpsproto)mentioning
confidence: 99%